Istiqomah dan Implikasinya dalam Kehidupan Muslim di Era Modern: Analisis Interpretasi QS. Fussilat Ayat 30 Perspektif Tafsir Al-Ibriz karya KH. Bisri Musthofa - Lia Nurma Wulandari; Aziz Miftahus Surur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
KH Bisri Mushofa’s Tafsir Al-Ibriz possesses linguistic characteristics that reflect a strategy to ground the sacred verses within the intellectual framework of the local community. The use of the Javanese language serves as a bridge between the sacred text and the social realities of the community, one of which is the moral issue that has now become a pressing concern within society. The crisis of consistency in worship and the decline in moral integrity are real challenges faced by Muslims in this modern era. Through the concept of istiqamah explained in Surah Fussilat verse 30, the Qur’anic verse offers a fundamental solution to the moral issues prevalent in the modern age. This study aims to analyze the concept of istiqamah and the reward promised by Allah to those who practice it, as interpreted in Tafsir Al-Ibriz by K.H. Bisri Musthofa, as well as to explore its implications for the lives of Muslims today. Translated with DeepL.com (free version). The results of the study indicate that K.H. Bisri Musthofa interprets istiqamah as total consistency encompassing the dimensions of tawhid (verbal), ibadah (action), and steadfastness of the heart (inner). The reward for those who practice istiqamah is the arrival of angels at the moment of death, who provide three assurances: peace of mind in facing death, ease in leaving this world, and the certainty of paradise. This interpretation affirms that istiqamah is not merely a ritual practice, but a spiritual foundation that guarantees true salvation. Its relevance to the contemporary context includes the formation of a Muslim character that is consistent, resilient, and of integrity amidst the various temptations of modernity.